The metaphysical espace of Borges’ universe - Kazmierczak, Marcin (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
The author of the article is carrying out an attempt of a synthetic approach towards the totality of the philosophical sources of Borges” literary universe, which guides him to the conclusion that the idealistic sources prevail over the materialistic and objectivist ones. Nonetheless, this does not mean that Borges may be called an “idealist”. The idealism, which undoubtedly turns out to be aesthetically most attractive to Borges, however, proves to be but a mental stage in his speculative itinerary, used by him to overcome the materialism but, later on, itis overcome on its own by the nihilism and skepticism in crescendo. The inquiry into the possible aesthetic and psychoanalytical criteria of this Borgesian tendency constitutes a supplement to these disquisitions.